2020
DOI: 10.3390/w12082250
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Oxidation of Humic Acids Using Platinum Electrodes: An Experimental Approach and Kinetic Modelling

Abstract: Humic acids (HA) are a potential hazard to aquatic ecosystems and human health. Because biological treatment of contaminated water does not satisfactorily remove these pollutants, novel approaches are under evaluation. This work explores electrochemical oxidation of HA in aqueous solution in a lab-scale apparatus using platinum-coated titanium electrodes. We evaluated the effects of HA concentration, current density, chloride concentration and ionic strength on the rate of HA oxidation. The initial reaction ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 77 publications
0
16
0
1
Order By: Relevance
“…Recently, electrochemical oxidation (EO) has gained much attention as a very effective method for removing a wide range of pollutants. Efficiency and green performances are the main reasons this technique is very reliable and widely used [15]. EO processes are characterized by two approaches called direct electro-oxidation, or anodic oxidation, and indirect electro-oxidation, as discussed in section 3.…”
Section: Electrochemical Oxidation (Eo)mentioning
confidence: 99%
“…Recently, electrochemical oxidation (EO) has gained much attention as a very effective method for removing a wide range of pollutants. Efficiency and green performances are the main reasons this technique is very reliable and widely used [15]. EO processes are characterized by two approaches called direct electro-oxidation, or anodic oxidation, and indirect electro-oxidation, as discussed in section 3.…”
Section: Electrochemical Oxidation (Eo)mentioning
confidence: 99%
“…EO is a technique belonging to the class of advanced oxidation processes (AOPs), which have proven to be very effective and reliable for removing emerging pollutants and NH 4 + -NH 3 from water [ 36 , 37 , 38 , 39 , 40 ]. The efficiency of the electrochemical treatments is influenced by several factors, including initial NH 4 + -NH 3 concentration, applied current intensity, pH, concentration and composition of the electrolyte, and type of anode material used [ 35 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the electrochemical treatments is influenced by several factors, including initial NH 4 + -NH 3 concentration, applied current intensity, pH, concentration and composition of the electrolyte, and type of anode material used [ 35 , 41 ]. Among these factors, the composition of the electrolyte, the applied current density, and the type of anode material used over the treatment are the most significant parameters impacting both efficiency of the process and the overall costs [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, to determine the corresponding dosage of chemical reagents. Besides, it is well-known that advanced oxidation processes can be used to reduce organic water pollution (Salvestrini et al 2020;Gallo-Cordova et al 2021;Januário et al 2021). For example, Liu et al (2019) reported that ozone-based advanced oxidation process (AOP) and in particular combination of UV with ozone and H 2 O 2 is efficient to degrade micropollutants.…”
Section: Introductionmentioning
confidence: 99%